Psychological and pedagogical aspects of consolidation of social capital of higher education institutions - Bocheliuk, Vitalii Y.; Nechyporenko, Valentyna V.; Pozdniakova-Kyrbiatieva, Ellina H.; Pozdniakova, Olena L.; Siliavina, Yuliia S. (Linguistics and Culture Review, 2021)
The aim of the study was to identify psychological and pedagogical factors that ensure the consolidation of social capital in higher education institutions and to assess their effectiveness through expert critical evaluations. The study used the exploratory design and was based on the use of qualitative methods to evaluate the selected studies. The research methodology relied on the methods recommended for feasibility studies to determine the possibility of implementation of the selected best practices. The systematic review of scientific sources and best practices found the psychological and pedagogical aspects that ensure the consolidation of social capital in higher education institutions, namely: individual psychological factors of economically motivated behaviour, social network technology, second-order psychological factors, teachers’ assistance of students’ professional self-determination, education as a means, and psychological factors based on the attributes of the institution. The results of expert evaluation of the above factors suggest that the last three ones mentioned have the potential for duplication, dissemination and transferability in higher education institutions in Ukraine.